PERAN BERPIKIR KRITIS DALAM MEMBANGUN ENTREPRENEUR MINDSET MAHASISWA DI PERGURUAN TINGGI - Zharifah, Nasywa; Rani Sukmadewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research is in-depth about the crucial role of critical thinking in shaping entrepreneurial mindset in university students. Through a quantitative method by distributing questionnaires to the heads of groups participating in the Unpad Independent Entrepreneurship Program 2023, this study analyses the impact of critical thinking skills on building a positive entrepreneurial attitude. The results showed a positive and significant correlation between critical thinking skills and entrepreneurial mindset. Students who are able to improve their critical thinking skills are more likely to have attitudes that support entrepreneurship. The findings provide important insights, highlighting the importance of critical thinking development in the context of higher education as a strategic step to support the development of entrepreneurship. Taking these findings into account, higher education institutions can design more effective learning strategies to prepare students for the challenges of the dynamic world of entrepreneurship. As a result, this research provides a foundation for designing educational programmes that are more adaptive and responsive to the needs of students in developing an entrepreneurial mindset.